Uji Brine Shrimp Lethality Test (BSLT) Ekstrak Etil Asetat Spons Calthropella sp. Asal Zona Intertidal Pantai Krakal Gunung Kidul Yogyakarta - Fitria Susilowati (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2017)
Sponge is one of the most prolific sources in regard of their secondary metabolites as bioactive compounds. This study aimed to isolate and investigate the toxicity of ethyl acetate extract of sponge Calthropella sp. from intertidal zone of Krakal Beach, Gunungkidul. The isolation was done by maceration with methanol:dichloromethane (1:2) v/v. The dichloromethane extract was evaporated and then partitioned in ethyl acetate:water (3:2 v/v). The interesting layer of ethyl acetate was evaporated to yield a viscous extract. The toxicity test was assessed by Brine Shrimp Lethality Test (BSLT). The isolation resulted 7 fractions of ethyl acetate: 71,1; 86,4; 69,3; 88,8; 78,7; 97,5; and 100,2 mg. BSLT showed the LC50 value of the ethyl acetate fractions on toxic and very toxic category.